The interplay of corporate social responsibility and corporate political activity in emerging markets: The role of strategic flexibility in non‐market strategies. (31st January 2019) - Kamasak, Rifat; James, Simon R.; Yavuz, Meltem
Abstract: Corporate social responsibility (CSR) and corporate political activities are complementary, and the coordinated management of corporate social responsibility and corporate political activities may lead to better firm performance. However, corporate social responsibility and corporate political activities should be aligned carefully to utilize this complementarity. Strategic flexibility, which is the ability of a firm to adapt to changes in the external environment and make necessary organizational modifications quickly, can help firms to align their corporate social responsibility and corporate political activities. This paper empirically investigates the political dimension and the interactive dimension which describes interactions between corporate social responsibility and corporate political activities together with strategic flexibility and their effects on firm performance through a study of 142 firms in Turkey using moderated multiple regression methods. The results show that, while the political dimension had an inverted U‐shaped effect on firm performance, indicating that only a moderate level of corporate political activities may improve financial performance, the interactive dimension had positive but limited implications for performance. Finally, it was found strategic flexibility plays a positive moderating role on the relationships between the interactive dimension and firm performance. It is concluded that complementarity between corporate social responsibility and corporate political activities which may result in better performance is contingent on strategic flexibility.